Effect of electrical stimulation and genotype on meat quality traits of Nellore and crossbreed cull cows - Ibrahim, Abdu (2023)
The Brazilian beef cattle supply chain has undergone technological modernization in its production systems, resulting in better productivity, meat quality and competitiveness. Electrical stimulation (ES) has been used as an innovation in the meat industry to improve meat tenderness and colour of beef carcass. The study aimed to evaluate ES and genotype’s effects on carcass pH and temperature decline and meat quality attributes of Nellore and crossbred beef cattle. Ten cows (5 Nellore and 5 ¾ Nellore × ¼ Holstein) were used. Following slaughter, exsanguinations, dressing, and evisceration processes, the carcasses were halved by splitting along the vertebral column, and the right sides of the carcasses were electrically stimulated with 5 impulses (7 s duration each, with a 2 s interval between pulses), constant voltage (300 V) at variable amps, and 45 Hz. Meat quality analyses were performed on samples obtained from longissimus dorsi muscle. There were no effects (P>0.05) of ES, genotype and their interaction on carcass pH and temperature, carcass weight loss, thawing and cooking losses, chemical composition, colour: L* (lightness), a* (redness), and b* (yellowness) values and shear force. Sarcomere length was influenced (P=0.029) by ES × genotypes interaction. The highest sarcomere length (2.13 µm) was observed in the ES crossbred genotype group, while NES Nellore genotype group, and ES Nellore group did not differ. The practice of ES should be adopted in crossbred genotype carcasses to avoid the cold shortening of the sarcomere. Keywords: Carcass pH. Meat colour. Meat tendernes